Analysis of anxiety levels and attitudes of nursing students toward the nursing profession during the COVID-19 pandemic - Bahcecioglu Turan, Gulcan; Ozer, Zulfunaz; Ciftci, Bahar (Wiley, 2021)
Purpose This study was conducted to analyze the anxiety levels and attitudes of nursing students for the nursing profession during the COVID-19 pandemic. Methods Data collection forms were sent online to nursing students of three different state or foundation universities in Turkey. In all, 456 individuals who answered the data collection forms were included in the study. Findings Study results revealed that the total average score for the Attitude Scale for Nursing Profession was 162 +/- 15.6. The Professional characteristics subdimension score average was 80.64 +/- 7.02. Furthermore, the state of choosing nursing profession subdimension score average was 50.05 +/- 9.23, whereas the Attitude for the general status of nursing profession subdimension score average was 34.38 +/- 2.97. Due to the pandemic, anxiety levels for the nursing profession were 4.86 +/- 2.76 (between 0 and 10). It was determined that nursing students who studied in cities where the virus was very common had a more positive attitude toward the profession. Anxiety levels of nursing students studying in cities where the virus impact was moderate and in cities where the virus presence was quite common were higher (p > 0.05). Practical Implications It was found that nursing students had a positive and high-level attitude toward the nursing profession. Furthermore, the results demonstrated that attitudes toward the nursing profession decreased significantly as anxiety increased.
Keywords: anxiety; attitude for profession; COVID-19; nursing student; pandemic